2013
DOI: 10.1242/jeb.096164
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between group size, huddling behavior and basal metabolism: an experimental approach in the social degus

Abstract: Mammals exposed to low temperatures increase their metabolic rate to maintain constant body temperature and thus compensate for heat loss. This high and costly energetic demand can be mitigated through thermoregulatory behavior such as social grouping or huddling, which helps to decrease metabolic rate as function of the numbers of individuals grouped. Sustained low temperatures in endothermic animals produce changes over time in rates of energy expenditure, by means of phenotypic plasticity. However, the puta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…When temperatures drop, animals start to metabolize and "spend" energy to warm up through for example through shivering. Shivering counts as one of the most energy-costly bodily processes and thus is expensive (King & Farner, 1961); it may then also not come as a surprise that animals seek to economize thermoregulation, so that body thermoregulation is done as efficiently as possible (Nuñez-Villegas et al, 2014). …”
Section: Thermoregulation In the Animal Kingdommentioning
confidence: 99%
See 1 more Smart Citation
“…When temperatures drop, animals start to metabolize and "spend" energy to warm up through for example through shivering. Shivering counts as one of the most energy-costly bodily processes and thus is expensive (King & Farner, 1961); it may then also not come as a surprise that animals seek to economize thermoregulation, so that body thermoregulation is done as efficiently as possible (Nuñez-Villegas et al, 2014). …”
Section: Thermoregulation In the Animal Kingdommentioning
confidence: 99%
“…Experimental rodent research has suggested a first hint to this energy-saving hypothesis for homeotherms: The Octodon Degus' (a Chilean rodent) energy usage at 15 degrees Celsius is 40% lower and surface temperature higher when housed with three or five (vs. alone; Nuñez-Villegas et al, 2014). This causes social thermoregulation to be part of homeotherms' essence, as one article reviewing rat research shows that social thermoregulation is one core reason for why homeotherms live in groups (Ebensberger, 2001).…”
Section: Thermoregulation In the Animal Kingdommentioning
confidence: 99%
“…Experimental data from a broad range of taxa show that there are at least four mutual benefits that can result from aggregation behaviour: (i) decreased chance of predation (Colbert et al, 2010;Creel et al, 2014;Unglaub et al, 2013), (ii) increased feeding efficiency (Horst, 1995;Jackson et al, 2008;Hsia and Wood-Gush, 1982;Lazarus, 1979), (iii) increased locomotion efficiency (Ebensperger and Bozinovic, 2000;Fish, 1995;Voelkl et al, 2015) and (iv) decreased energy spent on thermoregulation (Gilbert et al, 2008(Gilbert et al, , 2010Nunez-Villegas et al, 2014;Withers and Jarvis, 1980). However, aggregation behaviour may have more than one function within a single species (Lazarus, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…In rodents, social thermoregulation has been shown to be one of the most important motivating forces behind group living, especially when temperatures drop (Ebensperger, 2001). As but one example, the Octodon Degus (a Chilean rodent) used 40% less energy and achieved a higher surface temperature when housed with three or five others (versus alone; Nuñez-Villegas et al, 2014). Studies of vervet monkeys show somewhat more complex mechanisms, with larger social networks buffering their core temperatures from the cold (McFarland et al, 2015), while even grooming a dead vervet monkey’s pelt insulates against temperature variations (McFarland et al, 2015).…”
Section: Why Social Thermoregulation Is Vital For Co-regulation: the mentioning
confidence: 99%